2019
DOI: 10.12669/pjms.35.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of retinal nerve fiber layer thickness between normal population and patients with diabetes mellitus using optical coherence tomography

Abstract: Objective: To compare the difference in peripapillary Retinal Nerve Fibre Layer (RNFL) thickness between normal population and Type-II diabetic patients without diabetic retinopathy using Spectral Domain Optical Coherence Tomography (SD OCT). Methods: This cross sectional study was carried out at PNS Shifa Naval Hospital, from May 2017 to November 2017. Out of 200 eyes, 100 eyes were of normal individuals and 100 eyes were of Type-II diabetic patients without diabetic retinopathy. Both groups were age an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…Thickening of RNFL can also be caused by damage to the inner bloodretinal-barrier causing edema. 9,14,[18][19][20] This study found a positive moderate correlation (0.4 -<0.7) between peripapillary perfusion density and peripapillary RNFL thickness globally, and in the superior and inferior quadrants. A positively moderate correlation (0.4 -<0.7) was also found between the peripapillary flux index and peripapillary RNFL thickness globally, and in the superior and inferior quadrants.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Thickening of RNFL can also be caused by damage to the inner bloodretinal-barrier causing edema. 9,14,[18][19][20] This study found a positive moderate correlation (0.4 -<0.7) between peripapillary perfusion density and peripapillary RNFL thickness globally, and in the superior and inferior quadrants. A positively moderate correlation (0.4 -<0.7) was also found between the peripapillary flux index and peripapillary RNFL thickness globally, and in the superior and inferior quadrants.…”
Section: Discussionsupporting
confidence: 48%
“…In the study of Mase et al, the peripapillary perfusion density was significantly higher in the superotemporal and inferotemporal quadrants compared to other quadrants. 9,18,21,22 There were several limitations of this study. The method we used was cross-sectional, therefore it is difficult to determine the causal relationship between microvascular changes and neurodegenerative changes.…”
Section: Discussionmentioning
confidence: 95%
“…Both overall and superior RNFL thickness correlated with the age of T1D patients in the Dehghani et al study, at the same time being an indicator of peripheral neuropathy in the patients [20]. In other research, the significant thinning of RNFL and its individual quadrants was confirmed in T2D patients without retinopathy in comparison to the controls [21]. Furthermore, there are also studies in which RNFL thinning was found to correlate with the severity of retinopathy, but it was found also in T2D patients [22].…”
Section: Discussionmentioning
confidence: 88%
“…DR is a combination of microvascular abnormalities and neurodegenerative changes in the retinal ganglion cells [ 25 , 26 ]. Previous studies showed that the mean four-quadrant p-RNFL was thinner in NDR patients than in controls [ 27 , 28 ]. Sohn et al.…”
Section: Discussionmentioning
confidence: 99%